Response Surface Optimization of Acetylcholinesterase Extraction from Scomberomorus commerson for Toxicological Applications (Journal of Environmental Microbiology and Toxicology, 2025)
Cholinesterase, especially acetylcholinesterase, is often used in toxicology research in insecticide biomonitoring work from the environment or from agricultural products. One of the most utilized sources of acetylcholinesterase is from fish acetylcholinesterase, and the search for potentially sensitive sources of acetylcholinesterase is ongoing research. In this study, the extraction conditions of acetylcholinesterase (AChE) from Scomberomorus commerson, a novel source, were optimized using Response Surface Methodology (RSM). A Box-Behnken Design (BBD) was applied to evaluate the effects of three independent variables—pH (7.0-8.8), NaCl concentration (0.05-0.20 M), and Triton X-100 concentration (0.01-0.04% v/v)—on AChE activity as the response. Experimental data were fitted to a quadratic polynomial model, which demonstrated good agreement with the observed values (R² = 0.9081; Adj R² = 0.7898). Analysis of variance confirmed that pH was the most significant factor influencing extraction efficiency (p < 0.01), while NaCl and Triton X-100 showed weaker individual effects within the studied range. A significant interaction between pH and NaCl (p < 0.05), together with the quadratic effect of pH, contributed to the nonlinear extraction profile. Numerical optimization predicted maximum AChE activity at pH 8.79, 0.197 M NaCl, and 0.039% Triton X-100, yielding a predicted activity of 0.145 U (95% CI: 0.125-0.166 U). Experimental validation produced a similar value of 0.152 U, confirming the reliability of the model. Further kinetic characterization revealed substrate-dependent variations in catalytic parameters, with Vmax and Km values of 0.02238 U and 0.03387 mM for acetylthiocholine (ATC), 0.02135 U and 0.2177 mM for propionylthiocholine (PTC), and 0.01928 U and 0.2316 mM for butyrylthiocholine (BTC), respectively. These findings demonstrate that RSM is an effective approach for improving AChE extraction, with pH identified as the primary factor governing extraction performance.
Keywords: Acetylcholinesterase (AChE); Extraction optimization; Response Surface Methodology (RSM); Box-Behnken Design (BBD); Toxicology biomonitoring